EKSPLORASI KUALITAS PROFESIONAL DI BIDANG SISTEM INFORMASI AKUNTANSI - Hermawan, Hendy (Jurnal Ekonomi Modernisasi, 2010)
The usage of Information technology in universities is to facilitate the adminstrative and educational process. Computer, database, student information system are used to facilitate the administrative process. Correspondence and archiving have already been performed by means of computer and printer. In big cities, it is seldom to find a university that still uses typing machine rather than computer to make a letter. Nevertheless, computer is not just the substitute of typing machine. When computer is not available, the administrative process is realy essential in many universities. The purpose of this research is analayze factors that affect quality of professional accounting information system. The factors that affect quality of professional accounting information system are business knowledge, system development application, user support, programming and system planning. The sample of this research 142 end-user respondent. The result of this research show that business knowledge, system development application, user support, programming and system planning affect the quality of professional accounting information systemÂ